Pharmacological and structural studies on the hedgehog pathway receptor smoothened - Klindert, S (2023)
The Frizzled-class G protein-coupled receptor Smoothened (SMO) is an essential component of the Hedgehog (HH) signalling pathway, which is of paramount importance to developmental processes of bilaterians. Dysregulation of HH signalling has been implicated in multiple pathophysiological processes in adult organisms, such as cancer development. SMO is targeted by multiple anti-cancer drugs, but resistance mutations were reported to decrease inhibitor potency and adverse events force medication discontinuation. While structural and functional studies have furthered our understanding of how SMO is regulated, details of SMO activation mechanisms and the interplay between the multiple SMO ligand-binding sites remain to be further clarified. Furthermore, there is limited information on the mechanisms of downstream signal transduction of vertebrate SMO, which most likely involve the G protein-coupled receptor kinase 2 (GRK2). This thesis describes the work we conducted to contribute to answering these questions, and to the development of next-generation SMO inhibitors. We optimised sample preparation to determine high-resolution structures of inactive SMO from human and fly, and of activated human SMO in complex with the essential downstream pathway component GRK2. Our findings will aid future structural studies on SMO by single particle cryogenic electron microscopy (cryo-EM). Ultimately, these cryo-EM structures will provide insights into the evolutionary divergence of SMO activation mechanisms, and into the mechanisms of vertebrate HH signal transduction. Moreover, we conducted functional characterisation of novel HH pathway inhibitors, which were identified in collaborative projects by high-throughput screening and computational docking. These resulted in the identification of six small molecule series that can inhibit HH signalling, three targeting the SMO extracellular cysteine-rich domain (CRD), and three potentially targeting the transmembrane domain (TMD). The ligands targeting the SMO CRD inhibit vismodegib-resistant mouse SMO-D477G, and are currently undergoing medicinal chemistry optimisation to ultimately enable potential therapeutic applications. Furthermore, these compounds can be used in future structural and functional studies to clarify how SMO selects between different downstream HH pathway effectors.